Effect of genetic elimination of seed lipoxygenases on agronomic characteristics of soybean - Martins, Carlos Alberto Osório; Sediyama, Carlos Sigueyuki; Moreira, Maurílio Alves; Reis, Múcio Silva; Rocha, Valterley Soares; Oliveira, Maria Goreti de Almeida (Pesquisa Agropecuaria Brasileira, 2002)
The genetic elimination of lipoxygenase (Lox 1, Lox 2 and Lox 3) enzymes from soybean seeds is a way to overcome the problems associated with the undesirable beany flavor of soybean seeds. Aiming at elucidating the influence of this genetic elimination on the agronomic characteristics of the soybean plants and grain yield components, the commercial variety of soybean FT-Cristalina RCH and its backcross derived lines, lacking the three lipoxygenases in the seeds (triple-null) and with these enzymes (triple-positive) were evaluated at three sowing dates. The commercial variety was more homogeneous than the lines with or without lipoxygenases, indicating the presence of significant amount of genes of the non-recurrent progenitors in the lines, mainly in the triple-null. The different sowing dates evidenced more differences among genetic materials (commercial variety, triple-null and triple-positive lines), in plant characteristics and grain yield components. The genetic elimination of lipoxygenases of the seeds did not negatively affect the agronomic characteristics of FT-Cristalina RCH soybean variety.